Progesterone requires heat shock protein 90 (HSP90) in human sperm to regulate motility and acrosome reaction - Sagare-Patil, Vrushali (J Assist Reprod Genet, 2017)
PURPOSE: The aims of this paper were to study whether heat shock protein 90 (HSP90) is a regulator of sperm functions and to determine its association with oligoasthenozoospermia. METHODS: The levels of HSP90 in sperm lysates were measured by ELISA. Localization of HSP90 and its isoforms was evaluated by immunofluorescence. Sperm motility and kinetics were assessed by computer-assisted sperm analysis. Acrosome reaction was determined by lectin staining. RESULTS: The levels of HSP90 were lower in oligoasthenozoospermic men and correlated positively with the number of motile spermatozoa. In capacitated human spermatozoa, HSP90α was mostly found in residual nuclear envelope, and the HSP90β isoform was higher in the flagella. Inhibition of HSP90 by geldanamycin or 17-AAG did not affect basal motility, but suppressed progesterone-mediated forward progressive motility, hyperactivation and acrosome reaction. Progesterone treatment dephosphorylated both HSP90α and HSP90β at Ser/Thr-Pro residues, but not Tyr residues. CONCLUSION: HSP90 levels are downregulated in oligoasthenozoospermia, and its functional inhibition attenuates progesterone-mediated sperm motility and acrosome reaction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10815-017-0879-5) contains supplementary material, which is available to authorized users.